The effects of kinesio taping on rate of force development in squat jump and counter movement jump - Shen, C. T.; Huang, P. T.; Chang, J. H. (ISBS Proceedings Archive (Michigan), 2017)
Kinesio tape (KT) has been widely used to prevent muscle pain and to improve strength and sports performance. Therefore, the aim of this study was to investigate the effect of KT in rate of force development (RFD). To compare with KT or non-KT in squat jump (SJ) and counter movement jump (CMJ). The RFD was improved or not improved by using KT. Six healthy female was recruited in this study. The kistler force plate was used to measure the RFD. There is no significant improve in SJ and CMJ. The results showed that KT did not affect RFD.